Strategi Pengembangan Objek Wisata Karacak Valley Berbasis Blue Ocean Strategy - Rina Kurniawati; Andri Ikhwana; Erni Anggraeni (Jurnal Kalibrasi, 2022)
This research was conducted with the aim of knowing what factors are the strengths, weaknesses, opportunities and threats of the Karacak Valley tourist attraction and recommending development strategies that must be carried out to increase the success of the Karacak Valley tourist attraction. This study applies SWOT Analysis and Blue Ocean Strategy, to evaluate strengths, weaknesses, opportunities, and threats, to identify internal and external potential of a tourist attraction. The implementation of the Blue Ocean Strategy aims to implement new market space where competitors have not yet implemented it, to implement demand and increase opportunities that are very profitable for the Karacak Valley. This study resulted that the Karacak Valley tourist attraction has two initial strategic factors in determining the strategy, namely IFAS (internal factor analysis strategy) and EFAS (external factor analysis strategy). It is found that the position of the Karacak Valley tourist attraction is included in quadrant I, which means that the company has advantages with strengths and opportunities, so this aspect needs to be utilized. This implementation needs to focus on an aggressive growth policy (Growth Oriented Strategy). The results of this research are the development strategy of the Blue Ocean Strategy, in which Karacak Valley can develop tourism objects to get out of the Red Ocean Strategy, namely by increasing the quality of tourist attractions, improving environmental cleanliness, improving service, security, and increasing access to make it easy to reach. Another strategy is by (divergence) where the company goes further than its competitors by innovating. The resulting innovations include creating rides for games, creating information system websites, making attractive promotions on social media, and building glamping grounds.